Socialization of The Importance of Procurement of Government Goods and Services for The Young Generation: Sosialisasi Pentingnya Pengadaan Barang dan Jasa Pemerintah Bagi Generasi Muda - Mahmud, Soni Fajar; Faisal, Rudi; Sari, Febrina (Institut Riset dan Publikasi Indonesia, 2024)
Knowledge regarding government procurement of goods and services is an important aspect in ensuring transparency, accountability and efficient use of the state budget. For young people, a deeper understanding of this process not only supports their active participation in monitoring and evaluation, but also strengthens the integrity of the government system. However, based on the results of the implementation team's observations and interviews with the younger generation, namely students at SMK Negeri 1 Dumai, it was found that 70% of them did not have knowledge and had limited access to information related to government procurement of goods. and services, the proposed solution includes increasing knowledge through outreach activities regarding understanding, roles and procedures regarding the procurement of goods and services carried out by the government. The results of the evaluation of community service activities carried out by the implementing team through written tests showed that 90% of students understood how government procurement of goods and services was carried out, the importance of compliance with regulations and the positive impact on the economy and society